IDENTIFIKASI KEARIFAN LOKAL SEBAGAI UPAYA UNTUK MENINGKATKAN DAYA TARIK WISATA GREEN VILLAGE GEDANGSARI DI KABUPATEN GUNUNGKIDUL - Sugiarto, Eko; Haryanti, Dian (Kepariwisataan: Jurnal Ilmiah, 2017)
This study aims to identify local wisdom in Green Village Gedangsari, Gunungkidul Regency. This research uses qualitative method with combined data collection technique, there are observation, interview, and documentation. Some invention that have been identified as the findings of this research are (1) Tourism development in Green Village Gedangsari; (2) Some of the taboos that local people believe; (3) Local culinary; (4) The place of the sacred; (5) Nyadran and Rosulan Traditions; and (6) 4G development plan by Gedangsari community. These findings have the potential to increase tourist attraction in the Green Village Gedangsari region.